GENDERED SOCIAL ROOTS OF HOMELESSNESS AMONG WOMEN VETERANS. Issue 2 (November 2013) - Hamilton, Alison B.; Washington, Donna L.; Zuchowski, Jessica L.; Besterman‐Dahan, Karen; Hamilton, Alison
<x xml:space="preserve">Abstract</x> Homelessness is one of the most challenging issues facing U.S. Veterans and those who serve Veterans. While the overall number of homeless Veterans is declining, the number of homeless women Veterans is increasing, with little clarity as to why. In previous work, we have examined pathways to homelessness among women Veterans, with a focus on proximal pathways, that is, how women perceived themselves to have become homeless at the time of the study. In this paper, we dig deeper into the roots of homelessness, specifically into the social institutional roots of homelessness. We examine women's focus group conversations about entering and experiencing the military, particularly with regard to the common occurrence of sexual violence and trauma before and during military service. Drawing on anthropological concepts, we conceptualize trauma at both an individual level as embodied in women's lived experiences, as well as at a collective, gendered level. Gendered traumatic experiences can accumulate over time, creating or reinforcing vulnerable pathways. For women Veterans, gender and the military are both social institutions that may act in combination to create gendered social roots of homelessness that are particular to women, and that may be relevant to the gender difference in prevalence of homelessness among Veterans.